Genetic rescue increases fitness and aids rapid recovery of an endangered marsupial population. Issue 1 (December 2017) - Weeks, Andrew; Heinze, Dean; Perrin, Louise; Stoklosa, Jakub; Hoffmann, Ary; Rooyen, Anthony; Kelly, Tom; Mansergh, Ian
Abstract Genetic rescue has now been attempted in several threatened species, but the contribution of genetics per se to any increase in population health can be hard to identify. Rescue is expected to be particularly useful when individuals are introduced into small isolated populations with low levels of genetic variation. Here we consider such a situation by documenting genetic rescue in the mountain pygmy possum, Burramys parvus . Rapid population recovery occurred in the target population after the introduction of a small number of males from a large genetically diverged population. Initial hybrid fitness was more than two-fold higher than non-hybrids; hybrid animals had a larger body size, and female hybrids produced more pouch young and lived longer. Genetic rescue likely contributed to the largest population size ever being recorded at this site. These data point to genetic rescue as being a potentially useful option for the recovery of small threatened populations. Genetic rescue can be valuable for the conservation of small populations threatened by low genetic diversity, but it carries the perceived risk of outbreeding depression. Here, Weeks et al. report increased hybrid fitness in a rescued population of the mountain pygmy possum, which likely contributed to population growth following genetic rescue.